Genetic structure and local adaptation of Neptunea cumingii crosse populations in China based on GBS technology - Tan, Bamei; Zhang, Dandan; Tian, Ying; Mao, Junxia; Wang, Xubo; Wang, Luo; Chang, Yaqing; Hao, Zhenlin (Frontiers in Ecology and Evolution, 2023)
To identify the genetic characteristics and local adaptation mechanism of the snail Neptunea cumingii in different sea areas of China, specimens from six coastal areas of the Yellow Sea and Bohai Sea were collected. Simplified genome technology was used to study the population genetic structure and genetic diversity level of N. cumingii and to infer the genetic variation pattern of environmental adaptation of this species. In total, 1992 discrete loci with high quality were obtained through quality control filtering and used for population genomics analysis. The observed heterozygosity was 0.1551–0.1612, and the expected heterozygosity was 0.1064–0.1117. Nucleotide diversity ranged from 0.1120 to 0.1241, and fixation index values ranged from –0.04683 to –0.02041. A total of 330 discrete loci were screened based on two fixation index values and a method associated with environmental factors. Functional annotation showed that the genes of 330 discrete loci were involved in the three major functions of cell composition, biological process, and molecular function, including growth and development and cell metabolism and catalytic activity. These results suggested that different populations of N. cumingii had loci that may be related to local adaptation. The results of this study helped clarify the level of genetic diversity and the germplasm genetic background of N. cumingii. They also provided information about the genetic mechanism of environmental adaptation of N. cumingii that can be applied to the restoration and management of N. cumingii resources.